Risk factors for human brucellosis in agro-pastoralist communities of south western Uganda: a case–control study - Asiimwe, Benon B. (BMC Res Notes, 2015)
BACKGROUND: Brucellosis is a zoonosis of veterinary, public health and economic significance in most developing countries. The disease can result in permanent and disabling sequelae and considerable medical expenses in addition to loss of income due to loss of working hours. A case–control study was conducted in Nyabushozi, Kiruhura district, Uganda, so as to determine the risk factors for transmission of brucellosis to humans in these communities. METHODS: We conducted a matched case–control study among participants in a previous study who were positive by the standard Serum Agglutination Test with titres ≥1:160. Controls were two neighbors for each case, matched by sex and age. A structured interviewer administered questionnaire was used to collect data on potential risk factors for brucellosis. Categorical variables were presented as proportions and their associations determined by Chi-square test. Bivariate analysis was performed to explore associations between the disease and the risk factors of brucellosis. Conditional logistic regression models were fitted to estimate independent associations between the disease and the risk factors using Odds Ratios and 95 % confidence intervals. RESULTS: A total of 45 cases and 90 controls were interviewed. Of the 45 cases, 21 (46.7 %) were male while 44/90 (48.9 %) of the controls were female. The most significant risk factors for infection being an agro-pastoralist (P = 0.05), consumption of raw cow ghee (P = 0.03) and consumption of unpasteurized milk (P = 0.02). CONCLUSION: The greatest risk factors for acquiring brucellosis in the study area were being an agro-pastoralist, consumption of raw cow ghee and consumption of unboiled milk. We recommend dissemination of health education packages regarding risks and prevention measures for brucellosis in these communities. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13104-015-1361-z) contains supplementary material, which is available to authorized users.